Konseling Kelompok dengan Terapi Realita dalam Menurunkan Prokrastinasi Akademik - Putri, Neneng Suryani (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2019)
This study aims to determine whether there is influence group counseling based on reality therapy to the level of student procrastination. Subjects in this study were MA MAFAZA amounting to 14 students. 7 people as experimental group and 7 people as control group. The data collection tools used in this research are: procrastination scale. Data analysis used is Wilxoccon Test which is a statistical method used to test the difference of 2 pieces of data in pairs that is between the control group and the experimental group. The results of analysis using SPSS through Wilxocon Test showed there were 6 samples whose academic procrastination rate was smaller after being treated compared to before. In the positive ranks column showed that no sample whose anxiety level increased after given treatment. While in the Ties column there is 1 sample showing that no change or decrease whatsoever after given treatment. The output shows that the value of P or Pv is 0.027. While the level of significant (α) research of 0.05. So the value of P <α or 0.027 <0.05 then Ho is rejected, it means there is influence of Group Counseling using Reality Therapy on the decrease of student academic procrastination